Monitoring and Evaluation of Human Trafficking Partnerships in England and Wales - Van Dyke, Ruth (Anti-Trafficking Review, 2017)
In the United Kingdom, human trafficking and, more recently, modern slavery has been pushed up the political and policy agenda. At the same time, partnership working has been promoted at international and national levels in order to encourage a more holistic response to trafficking. This article examines the nature of the evidence collected to monitor and evaluate the activities and outcomes of organisations involved in a number of human trafficking partnerships in England and Wales. Underpinning this analysis is the ‘4 Ps’ approach to tackling human trafficking: Prevention, Protection, Prosecution and Partnership. Based on interviews with a variety of actors working in different partner bodies, limitations of evidence in relation to both monitoring activities as well as evaluating outcomes emerged. These relate to inadequate data collection, lack of robust methods of data collection, untested assumptions, the complexity of gathering evidence which reflect human welfare oriented goals, and the sharing of evidence between partner organisations. A key finding is that current data and methods of data collection are inadequate for the purpose of measuring the effectiveness of anti-trafficking initiatives and partnerships. Another key finding is the way in which partnerships challenged received outcomes and expanded their focus beyond victims of trafficking or criminal justice goals. Finally, I explore whether criminal justice outcomes can be leveraged to foster deterrence, by interrogating what evidence might be needed.